Effects of Cartilage Oligomeric Matrix Protein on Bone Morphogenetic Protein‐2‐induced Differentiation of Mesenchymal Stem Cells. Issue 4 (November 2014) - Guo, Peng; Shi, Zhong‐li; Liu, An; Lin, Tiao; Bi, Fanggang; Shi, Mingmin; Yan, Shi‐gui
<x xml:space="preserve">Abstract</x> Objective To investigate the effect of overexpression of cartilage oligomeric matrix protein (COMP) on bone morphogenetic protein‐2 (BMP‐2) induced osteogenic and chondrogenic differentiation of mesenchymal stem cells (MSCs). In this study, we used liposomes to transfect MSCs with plasmid encoding COMP and then induced the transfected MSCs to differentiate in osteogenic and chondrogenic differentiation media containing BMP‐2. Methods MSCs transfected with plasmid DNA encoding recombinant human COMP were induced to differentiate into osteocytes and chondrocytes by BMP‐2. Real‐time polymerase chain reaction (PCR) assays of osteogenesis‐related markers (collagen type I alpha 1, runt‐related transcription factor 2, osteopontin, bone gla protein) and chondrogenesis‐related markers (collagen type II alpha 1, sry‐related high‐mobility group box 9, Aggrecan) was performed to evaluate the process of cell differentiation. Cell differentiation was evaluated by alkaline phosphatase (ALP) and Alizarin red S stains for osteogenic differentiation and alcian blue staining for chondrogenic differentiation. Results Real‐time PCR assay showed significantly greater COMP expression by MSCs when COMP gene had been transfected into the cells (P < 0.01). Overexpression of COMP down‐regulated expression of osteogenesis‐related markers and up‐regulated expression of chondrogenesis‐related markers. ALP staining and Alizarin red S staining were weakened, whereas alcian blue staining was enhanced. Conclusion Overexpression of COMP inhibits BMP‐2‐induced osteogenic differentiation and promotes BMP‐2‐induced chondrogenic differentiation. These findings may provide new insights for cartilage tissue engineering. The experiments in the present study were all in vitro, which has potential limitations. Further in vivo studies to investigate the effects of COMP in animal models are necessary, which will be the next step in our research.